A Qualitative Study on Danish Student Pharmacists’ Attitudes Towards and Experience of Communication Skills Training - Duijm, Neeltje P. (Pharmacy (Basel), 2019)
As the pharmacy profession evolves, good communication skills are vital for securing the safer and more rational use of medicines. Currently there is a lack of qualitative studies researching European student pharmacists’ and their experience with communication skills training (CST). This qualitative study aimed to fill this gap by exploring Danish student pharmacists’ attitudes towards, and experiences of, CST. Focus group interviews were conducted with a heterogeneous sample of Danish student pharmacists in 2016. Interviews were audio recorded, transcribed verbatim and analyzed inductively. Fifteen students participated in three focus groups. Five categories identified as key aspects were: professional communication vs. normal conversation, motivation to engage in training, how to learn communication skills, experience with CST and universities’ role in teaching communication skills. In conclusion, there were both positive and negative attitudes towards CST among the participants. However, they had little experience with CST. Bloom’s taxonomy of the affective domain and Kolb’s experiential learning model appear to be useful in understanding students’ attitudes towards CST. Pharmacy educators can use this study to structure and improve their CST curricula by knowing what influences students’ attitudes towards CST.